P.060 Immunoglobulin Use For Neuromuscular Conditions: Updating British Columbia Provincial Guidelines Through Focused Literature Review. (November 2021) - Tse, EK; Smith, CB; Chapman, KM; Beadon, K
Abstract : Background: Immune-mediated neuromuscular conditions often cause significant disability and may require ongoing immunomodulating therapies such as immunoglobulin (Ig). Ig use in several neuromuscular conditions such as Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) is supported by robust evidence, however Ig is increasingly used for other disorders. In British Columbia (BC), Ig use has increased annually; last year, expenditure exceeded 51 million dollars, 35% relating to neurological disease. Within the context of the pandemic, Ig supply is at risk of shortages. Methods: A focused literature review was conducted of CIDP, Guillain-Barré Syndrome (GBS), Multifocal Motor Neuropathy (MMN), Myasthenia Gravis (MG), and other neuromuscular conditions to compare BC Ig guidelines with international best practices. Provincial recommendations for Ig use were updated accordingly. Results: Evidence-based practices include acute and chronic Ig use in CIDP and MMN, and acute or relapse-related treatment in GBS and MG. Ig may be beneficial in other treatment-refractory inflammatory disorders such as Lambert-Eaton Myasthenic Syndrome and vasculitic neuropathy. Objective outcome measures can optimize patient care and ensure appropriate resource utilization. Conclusions: Updated BC guidelines emphasize using established diagnostic criteria, objective outcome measures and minimum effective Ig doses for neuromuscular conditions. Periodic literature reviews on Ig use allow guidelines to remain evidence-based.